A STUDY ON WORK LIFE BALANCE OF MARKETING PROFESSIONALS OF PHARMACEUTICAL INDUSTRY (Journal of Pharmaceutical Negative Results, 2022)
Keeping a work-life balance isn't so particularly key as it shows up. In the corporate world, change is unavoidably certain. The impact of globalization has moreover propped these changes. The corporate world is the exemplification of deficiencies, piles of liabilities, and long working hours. These advancements in the environment upset the balance between the home and work-life of the trained professionals. The rising test and mentioning of the overall people has also disturbed the situation. Everything adds up to the burnout.